Poor response to neoadjuvant chemotherapy in metaplastic breast carcinoma - Willard Wong; Edi Brogi; Jorge S. Reis-Filho; George Plitas; Mark Robson; Larry Norton; Monica Morrow; Hannah Y. Wen (npj Breast Cancer, 2021)
Abstract Metaplastic breast carcinoma (MpBC) is a rare special histologic subtype of breast carcinoma characterized by the presence of squamous and/or mesenchymal differentiation. Most MpBCs are of triple-negative phenotype and neoadjuvant chemotherapy (NAC) is frequently utilized in patients with MpBC. The aim of this study was to evaluate response to NAC in a retrospective cohort of MpBCs. We identified 44 patients with MpBC treated with NAC at our center between 2002 and 2018. Median age was 48 years, 86% were clinical stage II–III, and 36% were clinically node-positive. Most (80%) MpBCs were triple-negative or low (1–10%) hormonal receptor positive and HER2 negative on pre-NAC biopsy. While on NAC, 49% showed no clinical response or clinico-radiological progression. Matrix-producing subtype was associated with clinico-radiological response (p = 0.0036). Post NAC, two patients initially ineligible for breast-conserving surgery (BCS) were downstaged to be eligible for BCS, whereas three patients potentially eligible for BCS before treatment became ineligible due to disease progression. Only one (2%) patient had a pathologic complete response (pCR). Among the 16 patients presenting with biopsy-proven clinical node-positive disease, 3 (19%) had nodal pCR. Axillary lymph node dissection was avoided in 3 (19%) patients who had successful axillary downstaging. Residual cancer burden (RCB) was assessed in 22 patients and was significantly associated with disease-free survival and overall survival. We observed a poor response or even disease progression on NAC among patients with MpBC, suggesting that NAC should be reserved for patients with inoperable MpBC.